2021
DOI: 10.3390/jcm10112464
|View full text |Cite
|
Sign up to set email alerts
|

Human Nonmercaptalbumin Is a New Biomarker of Motor Function

Abstract: The ratio of human nonmercaptalbumin (HNA) and reduced albumin (HMA) may be a new marker for oxidative stress. Locomotive syndrome (LS) is reduced mobility due to impairment of locomotive organs. We investigated whether the HNA/HMA ratio could be a new biomarker of LS. This study included 306 subjects (mean age 64.24 ± 10.4 years) who underwent LS tests, grip strength, walking speed, and tests for HNA and HMA. Oxidative stress was measured by the ratio of HMA (f(HMA) = (HMA/(HMA + HNA) × 100)), and the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have reported that hypertension and smoking are risk factors for LS [17]. In addition, both LS and hearing loss are reportedly associated with oxidative stress [29]. We believe that lifestyle modifications, such as dietary modifications, including salt restriction and antioxidant intake, increased physical activity, and smoking cessation, may reduce the risk of LS and hearing loss.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have reported that hypertension and smoking are risk factors for LS [17]. In addition, both LS and hearing loss are reportedly associated with oxidative stress [29]. We believe that lifestyle modifications, such as dietary modifications, including salt restriction and antioxidant intake, increased physical activity, and smoking cessation, may reduce the risk of LS and hearing loss.…”
Section: Discussionmentioning
confidence: 76%
“…Ito et al reported that the ratio of nonmercaptalbumin (HNA) to albumin (HMA), a marker of metabolic stress, can be a biomarker for LS in elderly subjects (≥ 65 years) [ 26 ]. The results for the relationship between a high HNA/HMA ratio and a high LS stage were thought to be related to the increase in oxidative stress and the exacerbation of LS.…”
Section: Discussionmentioning
confidence: 99%